DESIGNING VIDEO GAME TO TEACH DESCRIPTIVE TEXT FOR TENTH GRADE AT SMAN 2 PONTIANAK - Muhammad Chandra Pratama Putera; Urai Salam; Eni Rosnija (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This research aimed at designing video game as english teaching and learning media to teach the descriptive text for the first semester students of tenth grade at SMA Negeri 2 Pontianak City of Kalimantan Barat Province. The writer used ADDIE as the research method and using analysis, design, and development in development research. Theparticipants of this research were the English teacher and also 34 students. The writer used questionnaire as the main instrument to collect the data to find out the usability of teaching media designed. The result of mean score of the questionnaire for the English teacher was 99% in strongly agreed, meanwhile the mean score of the questionnaire forthe students was 72,2% in agreed responds. In conclusion, the respond of the participants to the media designed was usable for the first semester students of tenth grade at SMA Negeri 2 Pontianak in academic year 2017-2018. Keywords: Descriptive Text, Design, Learning Media, Reading